Microorganisms of the marine corridor Isla del Coco-Galapagos: functional and species diversity - Rojas-Jiménez, Keilor (2018)
The marine corridor Isla del Coco-Galápagos, as a whole, constitutes a sanctuary for the protection of marine species in the eastern region of the Tropical Pacific. The high biodiversity of macroorganisms has been studied for decades, however, the diversity of phytoplankton microorganisms, which constitute the sustenance of life in this ecosystem, is not known at the same level of detail. In this work we use open access metagenomic data to examine the functional diversity of proteins and microbial species present in six points of this marine corridor. A very high diversity of microorganisms was identified, comprising 2132 genera distributed in 68 taxonomic phyla (6 Archaea, 33 Eukaryota, 38 Bacteria and 1 Virus). In particular, the most abundant taxa were Candidatus Pelagibacter, Prochlorococcus, Synechococcus, T4-like virus, and Pseudomonas, which coexist with a large number of poorly represented organisms. By similarity in their composition, the pelagic and coastal communities could be grouped, however, statistically there were no significant differences among all the communities of the corridor. This work highlights the ecological importance of microbial phytoplankton for the ecosystem, and represents an additional justification protection for the corridor as a whole.